STUDI PROSES GEOMORFOLOGI DENGAN PENDEKATAN ANALISIS UKURAN BUTIR SEDIMEN (Studi Kasus Proses Sedimentasi Muara Sungai Banyuasin Sumatera Selatan) - Rena Misliniyati (Inersia: Jurnal Teknik Sipil, 2019)
Sedimentation in estuaries due to deposition of sediment material by geomorphological process that work. It is therefore necessary to study geomorphological process in order to provide an overview of the mechanisms of sedimentation (the process of sediment transport and deposition of material) that occurred. To determine the geomorphology of the most dominant influence on sedimentation in estuaries, the sediment grain size analysis was performed with a statistical approach, then making the relationship between sediment grain size distribution with populations of sediment occurs. In this study used dataestuary sediment grain size of Banyuasin river taken at three points on the mouth of the river estuary. The analysis showed that the dominant geomorphological process influence on sedimentation in the estuary of Banyuasin is fluvial process, where the transport and deposition of sediment carried by the power flow of the river. This is reflected in the values of statistics and sediment populations. The resulting statistical value indicates the condition of energy (power flow) which produces sediment at this location is relatively large, tend to be unstable and fluctuate rapidly. Sedimentary material that was found is dominated by saltation population, and population of suspension amount is less than 20%. This scale indicates that the river flow velocity of Banyuasin is large enough, so the population of saltation carried in large numbers to and deposited at the mouth of the estuary. Meanwhile, the finer particles (suspension population) will be led further into the sea. Population such conditions describes the characteristic of sediment grain size distribution in the fluvial environment of deposition.